Jordbruksdränering, kostnader och genomförande - Lindström, Hans (2008)
Underdrainage is a costly investment but often a necessity to maintain rationalized plant cultivation, one can also see underdrainage as insurance to successful plant cultivation. Late ripening crops, low yield and difficult tillage cultivation are examples on an insufficient drainage. (Kvarnemo 1983) A drained field rise in land price and the scheme of the tiled drains is seen as a value item.